Analisis Etika Dalam Pengadaan Barang/Jasa Pemerintah - Valentina, Vina (Prosiding, 2024)
Procurement of goods and services plays a crucial role in the implementation of national development, aiming to improve public services and foster both national and regional economic growth. Procurement is essential in development activities because it ensures that various needs for development projects are met accurately and efficiently. This encompasses everything from infrastructure, equipment, and technology to services that support various sectors of development and public services. Government procurement is used to ensure that government needs are met in an efficient, transparent manner, in line with ethical principles. The goal of government procurement is to create a competitive environment, ensure efficient budget use, support local economic development, and meet established quality and reliability standards. Adhering to basic ethical standards in government procurement is fundamental and should serve as a reference and guideline throughout the procurement process. This reflects the philosophy that government procurement is an effort to obtain desired goods or services using logical and systematic reasoning, while adhering to prevailing norms and ethics according to established procurement methods and processes. Procurement ethics are norms that govern actions that should be taken and actions that are prohibited in the execution of procurement of goods or services. In the context of procurement, basic ethics refer to the norms or rules that serve as the main guidelines for participants to conduct the procurement process in a fair, transparent, and accountable manner.